[OP.7D.06] RENAL HEMODYNAMIC CHANGES AFTER RENAL DENERVATION. (September 2016) - Schmieder, R.S.; Schmid, A.; Janka, R.; Ditting, T.; Veelken, R.; Uder, M.; Schmieder, R.E.; Ott, C.
Abstract : Objective: Stimulation of renal sympathetic nerves causes reduced renal blood flow. To elucidate whether renal denervation (RDN) affects renal perfusion, we analysed renal blood flow of parenchymal areas perfused by arteries that were non-treated versus treated with RDN. Design and method: In a pilot study 8 patients with treatment-resistant hypertension that had multiple renal arteries in either kidney were included. All patients underwent catheter-based RDN using the Symplicity FlexTM RDN System of the main renal arteries, but not of accessory renal arteries. Renal perfusion was measured noninvasively by magnetic resonance imaging on a 1.5-T scanner with arterial spin labelling before (day-1), after (day + 1) and again after 3 months (3 M) of RDN. Renal parenchyma was divided into areas that were perfused by renal arteries which were treated with RDN versus those areas perfused by accessory renal arteries not treated with RDN. Hence, every patient could serve at its own control with respect to changes of renal blood flow in the same kidney. In addition renal function was assessed by eGFR according CKD-Epi formula. Results: There was an acute increase of renal perfusion in areas supplied by arteries not undergoing RDN (day-1: 242.3 [229.2–263.2] vs. day + 1: 260.0 [243.5–296.6] ml/min/100 g, p = 0.008), which returned to baseline values after 3 M (257.0 [240.5–277.8] ml/min/100 g, p = 0.260). In contrast, renal perfusion did not change in areas supplied by arteries undergoing RDN in acute (day-1: 263.5 [245.9–273.6] vs. day + 1: 256.5 [242.9–273.5] ml/min/100 g, p = 0.953) and 3 M (245.4 [235.5–269.7] ml/min/100 g, p = 0.594). Accordingly, the acute change in renal perfusion between day-1 and day + 1 was significantly greater in parenchymal areas supplied by arteries without compared to areas with RDN (p = 0.014), but not after 3 M. Renal function assessed by eGFR did not change between day-1 and day + 1 (80.3 ± 20 versus 79.8 ± 20 ml/min/1.73m 2, p = 0.885) as well as after 3 M of RDN (80.8 ± 18 ml/min/1.73m 2, p = 0.889). Despite an average of 7.0 ± 1.5 antihypertensive drugs, baseline office BP was 157/85mmHg, and was reduced by −11/−7mmHg after 3 M of RDN. Conclusions: Our data indicate an acute increase of renal perfusion in renal parenchymal areas perfused by arteries with intact renal nerves, whereas no change occurred in parenchymal areas perfused by arteries after RDN.